Pengaruh Kualitas Sumber Daya Manusia terhadap Inovasi Organisasi di Sekretariat DPRD Kabupaten Pesisir Selatan - Qibty Veronica Rahma; Sinta Westika Putri (Lembaga Yasin AlSys, 2026)
The quality of human resources is a strategic asset that plays an important role in driving organizational innovation, particularly in government institutions that are required to improve the effectiveness and quality of public services. Although the influence of human resource quality on organizational innovation has been widely examined, most studies still focus on the private sector, while studies on public organizations, particularly within the Secretariat of the Regional House of Representatives (DPRD), remain limited. This study aims to analyze the influence of human resource quality on organizational innovation at the Secretariat of the DPRD of Pesisir Selatan Regency. This study used a quantitative approach with an associative survey design, involving 74 employees selected through total sampling. Data were collected through Likert-scale questionnaires and documentation, then analyzed using simple linear regression with the assistance of SPSS version 21. The results of the study show that human resource quality has a positive and significant effect on organizational innovation. Human resource quality, reflected in education level, work skills, productivity, and adaptability, contributes to increasing the organization’s capacity to generate and implement innovation. The conclusion of the study affirms that improving human resource quality is an important factor in promoting organizational innovation at the Secretariat of the DPRD of Pesisir Selatan Regency. The implications of this study provide theoretical contributions to the development of public administration studies concerning the relationship between human resource quality and organizational innovation, as well as practical implications for local governments in designing sustainable employee competency development programs.